Social indicators of satisfaction with health and health care. Some survey research examples from the United States. - Parkum, Virginia C. (My University, 1975)
Verf. beschreibt Methoden und Ergebnisse der Indikatorenfindung in den USA.
Keywords: Gesundheit; Sozialindikator; Gesundheitswesen